Effect of β-cyclodextrin deodorization on the volatile chemicals and functional properties of three types of gelatins - Yang, Lili; Zi, Ye; Shi, Cuiping; Chen, Jiahui; Xu, Jiamin; Wang, Xichang; Zhong, Jian (Frontiers in Nutrition, 2022)
The exploration of deodorization is important for the application of gelatin in food industry. In this work, the effect of β-CD deodorization on the volatile chemicals and functional properties of three types of gelatins (commercial porcine skin gelatin, cold water fish skin gelatin, and Chinese longsnout catfish skin gelatin) were studied. The results suggested the odors of commercial gelatins were significantly less than home-extracted gelatins. The β-CD deodorization efficiency was dependent on both β-CD concentration and volatile chemical. (E)-2-Octenal (C8H14O), 1-octen-3-ol (C8H16O), 2-pentyl-furan (C9H14O), and hentriacontane (C17H36) could be deodorized at low β-CD concentration (even at 2 mg/mL). The best β-CD deodorization concentration for 66.7 mg/mL of Chinese longsnout catfish skin gelatin was 30 mg/mL. β-CD addition could not change the gel forming ability and emulsion activity of gelatins, whereas it had different and concentration-dependent effects on the emulsion stability of gelatins. β-CD addition had no obvious effects on the droplet coalescence and liquid-gel transition behaviors, but had different effects on the creaming of the emulsions stabilized by three types of gelatins. The encapsulation of β-carotene did not significantly change the droplet trimodal size distribution and liquid-gel transition of fish oil-loaded emulsions. However, β-carotene might delay the droplet coalescence. The creaming stability of β-carotene/fish oil-loaded gelatin/β-CD-stabilized emulsions was dependent on the gelatins, β-CD, and β-carotene. Finally, the β-carotene retention in the emulsions was dependent not on β-CD addition but on the nature of the gelatins. These results provided useful information to understand the molecular deodorization behaviors and explore the deodorization of emulsifiers for food emulsions.